BIOAKTIVITAS Amomum compactum SOLAND EX MATON DAN PERSPEKTIF KONSERVASINYA - Dr. Marina Silalahi, M.Si (Jurnal Pro-Life, 2017)
Amomum compactum Soland ex Maton is native plant in Indonesia, which is used as medicine and spices. The use of plants as medicine and spices relates to its compounds of secondary metabolites esspecially the essential oil. This article aims to explain the uses and bioactivity of A. compactum. This article is based on literature offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Amomum compactum is an aromatic herbaceous plant that is used to asthma, cancer, antioxidant, and anti-bacterial. Consevation of A. compactum can be through in-situ and ex-situ to conserve of genetic diversity.Keywords: Kapulaga, Bioactivities, Amomum compactum, Antibacteria